ANALISA KLASIFIKASI DATA MINING PADA TINGKAT KEPUASAN PENGUNJUNG TAMAN HEWAN PEMATANG SIANTAR DENGAN ALGORITMA - Dinda Nabila Batubara; Agus Perdana Windarto (STMIK Budi Darma, 2019)
The purpose of the study is to provide recommendations for the satisfaction of visitors to the animal park using the C4.5 datamining classification data laminating technique. Data sources were obtained from interviews with the management of the Pematangsiantar City Animal Park and the giving of questionnaires to random visitors as many as 150 people. Attributes used as parameters for assessing visitor satisfaction include: Ease of access to locations (C1), Infrastructure Facilities (C2), Parking lots (C3), Security (C4), Service Officers (C5) and Cleanliness (C6). The results of processing the C4.5 method using the help of RapidMiner software are the attributes of infrastructure (C2) and service officers (C5) being the attributes that most influence the level of satisfaction of visitors to the park. And the performance data shown on the suitability of the C4.5 method with the satisfaction of visitors to the animal park is 95%Keywords: Datamining, Classification, C4.5 Method, Visitors, Satisfaction, Animal Park